Guillaume de Machaut's "Messe de Nostre Dame" in the context of fourteenth-century polyphonic music for the Mass Ordinary. - Linklater, Christina. (University of Ottawa (Canada), 2000)
It is widely held in the scholarly literature of music history that the Messe de Nostre Dame of Guillaume de Machaut is unique. While several other examples of polyphonic settings of the Mass Ordinary dating from approximately the same era do survive, they are distinct from Machaut's Mass in at least two respects. The Messe de Nostre Dame is attributed to a single, named composer, whereas most fourteenth-century Mass cycles are anonymous, or are thought to have been assembled from the repertories of several composers, or both. Further, few contemporary medieval cycles are copied as such, preserving instead the traditional organization of the kyriale, in which several Kyrie movements are grouped in one section, followed by a group of Gloria movements, and so on; Machaut's Mass, however, survives complete in five manuscript versions, all of which present its six movements in uninterrupted succession. Despite the comparative difficulty of assembling cycles from the largely anonymous and physically separate movements described above, though, a convincing case may be made (and has been) for the existence of several pre-modern polyphonic cycles besides the Messe de Nostre Dame. (Abstract shortened by UMI.)
Keywords: Music.